1H NMR to assess bioaccessibility and stability of designed astaxanthin nanoemulsions - S. Bautista-Hernández; M.P. Jiménez-Escobar; M.P. Rascón-Díaz; M. Jiménez-Fernández; C.I. Beristain; A. Sánchez-Medina; L.A. Pascual-Pineda (Applied Food Research, 2025)
High-concentration astaxanthin nanoemulsions (NEAX) were formulated using a mixture of soy lecithin and non-ionic surfactants with different hydrophilic-lipophilic balance (HLB) values. Nanoemulsions were prepared using high-power ultrasound. The surface properties of the emulsifiers, including their HLB value and surface tension, were related to the bioaccessibility and stability of the nanoemulsions. Additionally, proton nuclear magnetic resonance (1H NMR) was used to assess the stability of astaxanthin after in vitro digestion. Particle sizes of approximately 200 nm and a high astaxanthin concentration of up to 2.8 ± 0.02 mg/mL were achieved. A higher HLB significantly enhanced astaxanthin's stability and bioaccessibility during digestion. The high-HLB value nanoemulsion released 45 % of astaxanthin during intestinal digestion, compared to 4 % bioaccessibility in oil. Furthermore, NEAX achieves maximum bioaccessibility within the initial minutes of intestinal digestion and provides a sustained release throughout its passage through the intestine. The 1H NMR analysis showed that astaxanthin in the nanoemulsions did not undergo significant structural changes after digestion. These results showed how 1H NMR can be applied to assess astaxanthin delivery, when HLB-optimized interfaces are used to improve bioaccessibility (45 % vs. <6 % in oil) and stability. Hence, high-HLB nanoemulsions are a promising strategy to improve astaxanthin delivery, offering enhanced bioavailability for functional foods and nutraceuticals.